A comparison of 3-D computed tomography versus 2-D radiography measurements of ulnar variance and ulnolunate distance during forearm rotation. (June 2014) - Kawanishi, Y.; Moritomo, H.; Omori, S.; Kataoka, T.; Murase, T.; Sugamoto, K.
Positive ulnar variance is associated with ulnar impaction syndrome and ulnar variance is reported to increase with pronation. However, radiographic measurement can be affected markedly by the incident angle of the X-ray beam. We performed three-dimensional (3-D) computed tomography measurements of ulnar variance and ulnolunate distance during forearm rotation and compared these with plain radiographic measurements in 15 healthy wrists. From supination to pronation, ulnar variance increased in all cases on the radiographs; mean ulnar variance increased significantly and mean ulnolunate distance decreased significantly. However on 3-D imaging, ulna variance decreased in 12 cases on moving into pronation and increased in three cases; neither the mean ulnar variance nor mean ulnolunate distance changed significantly. Our results suggest that the forearm position in which ulnar variance increased varies among individuals. This may explain why some patients with ulnar impaction syndrome complain of wrist pain exacerbated by forearm supination. It also suggests that standard radiographic assessments of ulnar variance are unreliable.